Correlation between Procalcitonin, Erythrocyte Sedimentation Rate and Red-Cell Distribution Width with Outcomes in ALL - Nathalya Dwi Kartikasari; I. G.A.A Putri Sri Rejeki; I Dewa Gede Ugrasena (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Acute Lymphoblastic Leukemia (ALL) increases annually and the incidence is mostly found in children. Its high failure rate is due to infection in the induction phase of chemotherapy. One of the strategies is laboratory testing to determine prognostic factors or predictors that can help clinicians determine therapy and outcomes in ALL. Research related to Procalcitonin (PCT), Erythrocyte Sedimentation Rate (ESR), and Red-cell Distribution Width (RDW) test in ALL children with poor outcomes has never been performed at Dr. Soetomo Hospital, Surabaya. This study aimed to determine the correlation of some infection parameters (PCT, ESR, and RDW) with outcomes in ALL. This was a cross-sectional study in the Pediatric Ward of the Dr. Soetomo Hospital in the period of June-August 2019. A total of 34 ALL patients after the induction phase of chemotherapy according to ALL-2018 protocol were included in this research. Procalcitonin, ESR, and RDW were determined using an ELFA method, photometrical capillary stopped-flow kinetic method, and flow cytometry method. The age of the study subjects ranged from 3 months to 16 years old, 32 patients (94.1%) were categorized as ALL-L1, 23 patients (67.6%) used protocol of high-risk group stratification. The study subjects were divided into 10 patients with poor outcomes and 24 patients with a good outcome. Procalcitonin was (2.66±13.15), ESR was (22.65±19.18), and RDW was (14.97±2.727). There was a significant correlation between PCT and outcomes.